Do marketing margins change with food scares? Examining the effects of food recalls and disease outbreaks in the us red meat industry - Hernandez, Manuel A.; Colin-Castillo, Sergio; Capps, Oral, Jr. (International Food Policy Research Institute, 2011)
This paper examines the impact of food scares on marketing margins in the US beef and pork industry. We analyze how market stresses induced by different food recalls and disease outbreaks affect price margins and the extent of price transmission at the slaughter-to-wholesale and wholesale-to-retail levels. We use monthly data for the period 1986-2008. The results indicate that marketing margins are differentially affected by Food Safety and Inspection Service (FSIS) recalls and bovine spongiform encephalopathy (BSE) outbreaks at different levels of the beef and pork marketing chain, although the effects are generally quite modest. Only BSE discoveries in the United States considerably affect marketing margins in the beef industry, specifically at the wholesale-to-retail level, as well as the extent of price transmission at the bottom of the beef and pork marketing channel. We also find that food safety incidents have minor cross-industry and cross-country effects on marketing margins.